Hiking-related orthopaedic injuries: Another epidemic during the COVID-19 pandemic - Wing Yiu Claudia Chu; Yau Chun Chong; Wing Yuk Mok (Journal of Orthopaedics, Trauma and Rehabilitation, 2021)
Introduction Coronavirus disease 2019 (COVID-19) had spread to over 200 countries and regions across the world since early 2020. Travel bans had been implemented in Hong Kong to control the spread of virus. Despite the burden to the healthcare system brought by COVID-19, there was also an increase in number of hiking-related injuries requiring inpatient care. The aim of this study is to report the incidence of hiking-related injuries admitted to the orthopaedic wards during the COVID-19 pandemic and comparison with statistics from the past years. Methods Data was retrieved from the admission books of the orthopaedic wards and Electronic Patient Records. The number of admissions, patients’ demographics and details of hospitalisation were compared between February to May 2020 (COVID-19 study period) and 2019. Secondary analysis was performed on admissions for tibia and/or fibula fractures with or without operation during the study period and compared with the past five years. Results 48 patients were admitted due to hiking-related conditions during the COVID-19 study period, which was 2.4 times more than 2019. 23 patients suffered from tibia and/or fibula fractures and was higher than the past five years (average 5.8, p = 0.0001). Among patients operated for tibia and/or fibula fractures, the percentage of hiking-related injuries was 41.9% in 2020 and 6.9% in the past five years (p = 0.0002). Conclusions An increase in incidence of hiking-related orthopaedic injuries was observed during the COVID-19 pandemic. Healthcare workers, public health experts and government officials should work together to raise awareness on safety in hiking for effective prevention of injury.